Heterogeneity in Staggered Wage Bargaining and Unemployment Volatility Puzzle - Engin Kara; Yongmin Park (Center for Economic Studies and ifo Institute (CESifo), 2017)
It has been noted that the search and matching model cannot account for the observed unemployment fluctuations. Gertler and Trigari (2009) show this weakness of the model disappears when wage stickiness is introduced to the model. Pissarides (2009) disagrees with this modification, arguing that new hires' wages are not sticky. We argue that there is heterogeneity in wage setting: while some wages are sticky, the others are not. We generalise the model to account for this heterogeneity. We find that the new model with even only a small fraction of sticky wage contracts comes closer to matching the data.
Keywords: E24; E32; J64; 330; search and matching; heterogeneity in staggered wage bargaining; unemployment volatility puzzle